Pharmacokinetics of co-formulated mefloquine and artesunate in pregnant and non-pregnant women with uncomplicated Plasmodium falciparum infection in Burkina Faso. - Valea, I; Tinto, H; Traore-Coulibaly, M; Toe, L; Lindegardh, N; Tarning, J; Van Geertruyden, J; D'Alessandro, U; Davies, G; Ward, SA (Oxford University Press, 2014)
OBJECTIVES: Mefloquine/artesunate has recently been developed as a fixed-dose combination, providing a promising rescue/alternative treatment for malaria during pregnancy. However, limited data are available on the effect of pregnancy on its pharmacokinetic properties. This study was conducted to assess the pharmacokinetic properties of mefloquine/carboxymefloquine and artesunate/dihydroartemisinin in pregnant and non-pregnant women with uncomplicated malaria. METHODS: Twenty-four women in their second and third trimesters of pregnancy and 24 paired non-pregnant women were enrolled. All patients were treated for uncomplicated Plasmodium falciparum malaria with a standard fixed-dose combination of oral mefloquine and artesunate one daily over 3 days. Frequent blood samples were collected before treatment and at scheduled times post-dose for the drug measurements and pharmacokinetic analyses. The study was registered at www.clinicaltrials.gov (identifier: NCT00701961). RESULTS: The total median exposure to mefloquine and dihydroartemisinin was not significantly different between the pregnant and non-pregnant women (P>0.05). There was a trend of higher exposure to mefloquine in the pregnant women, but this difference did not reach statistical significance (656700 versus 542400 h × ng/mL; P=0.059). However, the total exposure to carboxymefloquine was 49% lower during pregnancy (735600 versus 1499000 h × ng/mL; P<0.001) and the total drug exposure to artesunate was 42% higher during pregnancy (89.0 versus 62.9 h × ng/mL; P=0.039) compared with non-pregnant controls. CONCLUSIONS: The plasma levels of mefloquine and dihydroartemisinin appeared to be similar in both pregnant and non-pregnant women, but there were significant differences in carboxymefloquine and artesunate exposure. The data presented here do not warrant a dose adjustment in pregnant patients, but an extensive analysis of the data could provide a better understanding of these findings.